Reverend Dr. Martin Luther King, Jr. March in Downtown Fresno to Saroyan Theatre - Watkins, Howard::::::::: (1985)
Left side of front line of marchers: ??, Chris Petersen, Rev. ?, William Brewster, Karen Humphrey, Daniel Whitehurst and ?